Composite fiber for crack-resistant reinforced asphalt concrete, asphalt concrete and preparation method of composite fiber

Three -dimensional network structure composite fibers formed by the use of modified basalt fiber and lignin fiber, combined with polyester fiber or polypropylene fiber, solved the problem of insufficient cracking in the existing fiber in the asphalt mixture. Crack resistance and reduction of asphalt dosage.

CN119349916APending Publication Date: 2025-01-24SHANXI EXPRESSWAY DEV CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411462083.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing fibers have insufficient crack resistance in asphalt mixtures, and there are problems such as high energy consumption, unfriendly environment and high prices during the production process.

Method used

The three -dimensional network structure composite fiber formed by modified basalt fiber and lignin fiber through layers is combined with polyester fiber or polypropylene fiber as an organic enhanced body to form a complex with a multi -layer structure.

Benefits of technology

Improve the crack resistance of asphalt mixture, enhance the plasticity, toughness and damage tolerance of the material, reduce the amount of asphalt, and reduce the oil absorption rate of composite fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005092126780000051
    Figure BDA0005092126780000051
Patent Text Reader

Abstract

The invention discloses a composite fiber for anti-crack reinforced asphalt concrete, the composite fiber is of a multi-layer structure formed by compounding inorganic fiber and organic fiber, and the inorganic fiber and the organic fiber form an interlaced three-dimensional network structure matrix in a layered alternate superposition mode, the surface of the three-dimensional network structure matrix is coated with an organic reinforcement body, and interlayer gaps between the inorganic fibers and the organic fibers are filled with the organic reinforcement body; the composite fiber forms a composite body with a multi-layer structure in a layered alternate overlapping manner, so that the plasticity, toughness, damage tolerance and other properties of the material are improved under the condition of ensuring that the fiber material exerts own advantages, the crack resistance of the asphalt mixture can be improved, and the service life of the asphalt mixture is prolonged. Due to the network structure, the asphalt mixture can form an efficient dispersion channel in the composite fiber material, the purpose of remarkably improving the high and low temperature performance of the asphalt mixture by adding a small amount of the composite fiber material is achieved, and meanwhile the low oil absorption rate is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of asphalt mixtures, and in particular to a composite fiber for crack-resistant and reinforced asphalt concrete, asphalt concrete and a preparation method thereof. Background Art

[0002] Pavements paved with asphalt mixtures have the advantages of comfortable driving, convenient maintenance, and good road performance. Therefore, they are widely used in highway construction. However, due to environmental factors, increased traffic volume and traffic load, asphalt pavements are prone to cracking, which in turn affects driving safety. At present, there are two main solutions to the problem of asphalt pavement cracking: one is to use high-performance native asphalt or modified asphalt, but it is not economical in actual use; the other is to add a certain amount of fiber to the asphalt mixture to play a bridging role between asphalt and mineral materials, thereby improving the crack resistance of the asphalt mixture. The fibers used are generally divided into mineral fibers, plant fibers, and composite fibers. Mineral fibers are currently widely used fibers. Although mineral fibers have the advantages of high strength and large modulus, they have the disadvantages of high energy consumption in the production process, unfriendly to the environment, and high prices. Although plant fibers have a wide range of sources and are environmentally friendly, their strength is not high and they cannot improve the crack resistance of asphalt mixtures well. Composite fibers are made by physically blending several matrix fibers. Although they can exert their respective strength and oil absorption to a certain extent, they also sacrifice some intrinsic properties of the matrix material, that is, the plasticity, toughness, damage tolerance and other properties are reduced. At the same time, the unevenness of load distribution and the incoordination of deformation in the composite material are more significant, and cracks are easily initiated and expanded at the phase interface, which restricts the further improvement of the performance of the composite material and thus limits the use scenarios of the composite material.

[0003] Therefore, it is necessary to solve the problem of crack resistance of fibers used in asphalt mixtures. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a composite fiber for crack-resistant reinforced asphalt concrete, asphalt concrete and a preparation method thereof, so as to improve the crack resistance of asphalt mixture by the prepared composite fiber.

[0005] The composite fiber for crack-resistant reinforced asphalt concrete of the present invention is a multilayer structure composed of inorganic fibers and organic fibers, wherein the inorganic fibers and organic fibers are alternately stacked in layers to form a three-dimensional network structure matrix that is interwoven with each other, and the surface of the three-dimensional network structure matrix is ​​wrapped with an organic reinforcement, and the organic reinforcement is also filled in the interlayer gaps between the inorganic fibers and the organic fibers;

[0006] Furthermore, the inorganic fiber is modified basalt fiber, the organic fiber is lignin fiber, and the organic reinforcement is polyester fiber or polypropylene fiber;

[0007] Furthermore, the modified basalt fiber is a basalt fiber on which a layer of organic film is bonded in the form of chemical bonds;

[0008] Furthermore, the basalt fiber is modified by epoxy resin and nano-SiO2 particles;

[0009] Furthermore, the thickness of the organic film is 10-30 nm. ;

[0010] Furthermore, the mass ratio of the inorganic fiber, the organic fiber, and the organic reinforcement is 6-12:1:1-3;

[0011] Furthermore, the length of the composite fiber is 1-3 mm, and the mass percentage of flocculent fiber clusters is not less than 4.8%.

[0012] The present invention also discloses a method for preparing composite fibers for crack-resistant reinforced asphalt concrete, comprising the following steps: using basalt stone supplemented with part of blast furnace slag and artificial blocks as raw materials to prepare basalt fibers, spraying a mixed solution modifier of epoxy resin and nano-SiO2 particles on the surface of the basalt fibers, then mixing with lignin fibers at a temperature of 180-220°C, and finally adding an organic reinforcement and mixing evenly.

[0013] The present invention also discloses a crack-resistant reinforced asphalt concrete, which contains the composite fiber as described above. The raw materials of the asphalt concrete include the following components by weight: 40-70 parts of SBS modified asphalt, 500-600 parts of coarse aggregate, 100-300 parts of medium aggregate, 250-350 parts of fine aggregate, and 1-6 parts of composite fiber.

[0014] The present invention also discloses a method for preparing crack-resistant reinforced asphalt concrete, comprising the following steps:

[0015] S1, heat the aggregate to a temperature of 160°C-180°C and keep it warm for 3-4 hours;

[0016] S2, preheat the SBS modified asphalt to 165℃-175℃, then add the aggregate and composite fiber and mix well.

[0017] Beneficial effects of the present invention: The composite fiber for crack-resistant reinforced asphalt concrete, asphalt concrete and preparation method thereof of the present invention, the composite fiber adopts a layered alternating stacking method to form a composite with a multi-layer structure, based on the unique "shell" bionic structure (stacked layered structure), while ensuring that the fiber material plays its own advantages, while improving the plasticity, toughness, damage tolerance and other properties of the material, which can improve the crack resistance of the asphalt mixture, and the network structure of the composite fiber can enable the asphalt mixture to form an efficient dispersion path in the composite fiber material, so that the high and low temperature performance of the asphalt mixture can be significantly improved by adding a small amount of composite fiber material, and at the same time has a low oil absorption rate, which can reduce the amount of asphalt while improving the crack resistance of the asphalt mixture. DETAILED DESCRIPTION

[0018] For a better understanding of the present invention, the following examples are provided to further illustrate the present invention, but the present invention is not limited to the following examples.

[0019] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0020] The composite fiber for crack-resistant reinforced asphalt concrete of this embodiment is a multi-layer structure composed of inorganic fibers and organic fibers. The inorganic fibers and organic fibers are alternately superimposed in layers to form a three-dimensional network structure matrix that is interwoven with each other. The surface of the three-dimensional network structure matrix is ​​wrapped with organic reinforcements, and the organic reinforcements are also filled in the interlayer gaps of the inorganic fibers and the organic fibers. Based on the unique "shell" bionic structure, a three-dimensional network structure in which fiber layers are interwoven with each other is formed by alternately superimposing layers. The fiber materials can not only exert their own intrinsic properties, but also synergistically enhance and improve the properties of the composite materials in plasticity, toughness, damage tolerance and the like.

[0021] In this embodiment, the inorganic fiber is modified basalt fiber, the organic fiber is lignin fiber, and the organic reinforcement is polyester fiber or polypropylene fiber; the modified basalt fiber serves as the inorganic fiber layer, and is stacked and accumulated with the lignin fiber in layers to form a matrix with a three-dimensional network structure, and then composited with the polyester fiber or polypropylene fiber. The polyester fiber or polypropylene fiber is wrapped around the surface of the matrix, and the polyester fiber or polypropylene fiber is also filled in the interlayer gaps between the inorganic fiber layer and the organic fiber layer, thereby improving the interlayer bonding strength of the composite fiber and the integrity of the structure.

[0022] In this embodiment, the modified basalt fiber is a basalt fiber with a layer of organic film bonded in the form of chemical bonds; the basalt fiber is modified by epoxy resin and nano-SiO2 particles; the thickness of the organic film is 10-30nm; after the basalt fiber is modified, the fiber, which is originally inorganic, is bonded to a layer of organic film of a certain thickness in the form of chemical bonds. When it acts with asphalt materials, the "S bond" and epoxy functional groups on the fiber will combine with asphalt in the form of chemical bonds to produce chelating force, thereby improving the strength of the asphalt mixture. The modification of basalt fiber, on the one hand, optimizes the interfacial compatibility between the fiber and the resin matrix and enhances the interfacial bonding strength; on the other hand, it effectively eliminates static electricity during the fiber spinning process, promotes the compact molding of the fiber bundle, reduces damage caused by friction, and protects the fiber from environmental factors such as air, moisture and dust, maintaining its surface activity.

[0023] In this embodiment, the mass ratio of the inorganic fiber, the organic fiber, and the organic reinforcement is 6-12:1:1-3; preferably, the mass ratio of the inorganic fiber, the organic fiber, and the organic reinforcement is 9:1:2; the length of the composite fiber is 1-3 mm, and the mass percentage of the flocculent fiber group is not less than 4.8%, preferably, the length of the composite fiber is 2 mm, and the mass percentage of the flocculent fiber group is 4.8%. The moisture content of the composite fiber is 0.6%, and the pH value is 7.

[0024] The preparation method of the composite fiber for crack-resistant reinforced asphalt concrete of the present embodiment comprises the following steps: using basalt stone supplemented with part of blast furnace slag and man-made blocks as raw materials to prepare basalt fiber, spraying epoxy resin and nano-SiO2 particle mixed solution modifier on the surface of basalt fiber, then mixing with lignin fiber at a temperature of 180-220°C, and finally adding organic reinforcement to mix evenly. Using high-quality basalt stone supplemented with part of blast furnace slag and man-made blocks as raw materials, melt them in a furnace obtained by thermal power combined with a pool kiln, appropriately increasing the furnace temperature, the smelting temperature is 1450°C-1550°C, making the composition of the melt uniform, and fully volatilizing the gas generated inside the melt, then drawing and bundling through a platinum-rhodium alloy plate at a temperature of about 1350°C to obtain basalt fiber, and then modifying it with a mixed solution of epoxy resin and nano-SiO2 particles, and the mixed solution of epoxy resin and nano-SiO2 particles can also play a dispersing role. The basalt fiber is prepared by a high-speed four-roll centrifuge. During this process, the centrifuge speed needs to reach more than 8000rpm; the wind speed for auxiliary fiber formation needs to reach 200m / s. 5. The composite fiber is made by HiPerDiF device at 200℃ and 2MP. The moisture content of the composite fiber is 0.6% and the pH value is 7.

[0025] The crack-resistant reinforced asphalt concrete of this embodiment contains the composite fiber as described above, and the raw materials of the asphalt concrete include the following components by weight: 40-70 parts of SBS modified asphalt, 500-600 parts of coarse aggregate, 100-300 parts of medium aggregate, 250-350 parts of fine aggregate, and 1-6 parts of composite fiber. The coarse aggregate is 10-15mm graded crushed stone, the medium aggregate is 5-10mm graded crushed stone, and the fine aggregate is 2.6-3.5 machine-made sand. The needle penetration (25°C) of the SBS modified asphalt is 65.8, the softening point is greater than 90°C, the ductility (5°C, 5cm / min) is 45.2cm, and the density (25°C) is 1.038g / cm 3 When the composite fiber interacts with asphalt materials, the "S bond" and epoxy functional group on the fiber will combine with asphalt in the form of chemical bonds to produce chelating force, thereby improving the strength of the asphalt mixture. The composite fiber has a network structure that enables the asphalt mixture to form an efficient dispersion path in the composite fiber material, so that the high and low temperature performance of the asphalt mixture can be significantly improved by adding a small amount of composite fiber material. The composite fiber has a low oil absorption rate, which can reduce the amount of asphalt while improving the crack resistance of the asphalt mixture.

[0026] The method for preparing the crack-resistant reinforced asphalt concrete of this embodiment comprises the following steps:

[0027] S1, heat the aggregate to a temperature of 160°C-180°C and keep it warm for 3-4 hours;

[0028] S2, preheat the SBS modified asphalt to 165℃-175℃, then add the aggregate and composite fiber and mix well.

[0029] In the above embodiment, the gradation of the new composite fiber asphalt mixture used is shown in Table 1 below:

[0030]

[0031] Embodiment 1

[0032] The preparation requirements of the composite fiber asphalt mixture in this implementation are as follows: calculated by weight: 57 parts of SBS modified asphalt, 580 parts of coarse aggregate (10-15mm graded crushed stone), 200 parts of medium aggregate (5-10mm graded crushed stone), 220 parts of fine aggregate (2.6-3.5 machine-made sand), and 4 parts of new composite fiber.

[0033] Preparation of composite fiber anti-cracking reinforced asphalt concrete, the specific implementation process is as follows:

[0034] (1) Preparation of composite fibers

[0035] Step A1: Use high-quality basalt rock supplemented with some blast furnace slag and artificial blocks as raw materials, melt them in a 1450°C furnace (thermal power combined with pool kiln), appropriately increase the furnace temperature to make the composition of the melt uniform, and fully volatilize the gas generated inside the melt.

[0036] Step A2: The molten liquid is formed into fibers by a high-speed four-roll centrifuge (the centrifuge speed is above 8000 rpm), and the fibers are effectively dispersed and de-slaged by a high-speed high-pressure blowing suspension device (the blowing speed needs to reach 200 m / s).

[0037] Step A3: spraying a dispersant of a mixed solution of epoxy resin and nano-SiO2 particle type modifier on the surface of the basalt fiber.

[0038] Step A4: Using a HiPerDiF device, add lignin fibers at 200°C and 2MP to prepare a composite fiber matrix.

[0039] Step A5: Use high-speed and high-pressure blowing suspension equipment to add organic reinforcement (polypropylene fiber), and the organic reinforcement is evenly mixed and coated on the surface of the matrix fiber to form composite fiber. In this embodiment, the mass ratio of basalt fiber, lignin fiber and polypropylene fiber is 9:1:2.

[0040] (2) Preparation of asphalt concrete

[0041] Step S1: The ore material determined according to the grading design is kept in an oven at 160° C. for 4 hours;

[0042] Step S2: preheat the SBS modified asphalt to 165°C.

[0043] Step S3: adding the preheated mineral material and the novel composite fiber into the asphalt mixture mixing pot and dry mixing for 60 seconds.

[0044] Step S4: adding the SBS modified asphalt that has reached the preheating temperature into the mixing pot and stirring for 120 seconds to obtain a novel composite fiber anti-cracking reinforced asphalt mixture.

[0045] Embodiment 2

[0046] The composite fiber asphalt mixture of this embodiment includes, by weight, 57 parts of SBS modified asphalt, 580 parts of coarse aggregate (10-15 mm graded crushed stone), 200 parts of medium aggregate (5-10 mm graded crushed stone), 220 parts of fine aggregate (2.6-3.5 machine-made sand), and 4 parts of new composite fiber.

[0047] Preparation of composite fiber anti-cracking reinforced asphalt concrete, the specific implementation process is as follows:

[0048] (1) Preparation of composite fibers

[0049] Step A1: Use high-quality basalt rock supplemented with some blast furnace slag and artificial blocks as raw materials, melt them in a 1450°C furnace (thermal power combined with pool kiln), appropriately increase the furnace temperature to make the composition of the melt uniform, and fully volatilize the gas generated inside the melt.

[0050] Step A2: The molten liquid is formed into fibers by a high-speed four-roll centrifuge (the centrifuge speed is above 8000 rpm), and the fibers are effectively dispersed and de-slaged by a high-speed high-pressure blowing suspension device (the blowing speed needs to reach 200 m / s).

[0051] Step A3: spraying a dispersant of a mixed solution of epoxy resin and nano-SiO2 particle type modifier on the surface of the basalt fiber.

[0052] Step A4: Using a HiPerDiF device, add lignin fibers at 200°C and 2MP to prepare a composite fiber matrix.

[0053] Step A5: Use high-speed and high-pressure blowing suspension equipment to add organic reinforcement (polyester fiber), and the organic reinforcement is evenly mixed and coated on the surface of the matrix fiber to form composite fiber. In this embodiment, the mass ratio of basalt fiber, lignin fiber and polyester fiber is 9:1:2.

[0054] (2) Preparation of asphalt concrete

[0055] Step S1: The ore material determined according to the grading design is kept in an oven at 160° C. for 4 hours;

[0056] Step S2: preheat the SBS modified asphalt to 165°C.

[0057] Step S3: adding the preheated mineral material and the novel composite fiber into the asphalt mixture mixing pot and dry mixing for 60 seconds.

[0058] Step S4: adding the SBS modified asphalt that has reached the preheating temperature into the mixing pot and stirring for 120 seconds to obtain a novel composite fiber anti-cracking reinforced asphalt mixture.

[0059] Embodiment 3

[0060] The composite fiber asphalt mixture of this embodiment includes, by weight, 40 parts of SBS modified asphalt, 500 parts of coarse aggregate, 100 parts of medium aggregate, 250 parts of fine aggregate, and 1 part of composite fiber.

[0061] Preparation of composite fiber anti-cracking reinforced asphalt concrete, the specific implementation process is as follows:

[0062] (1) Preparation of composite fibers

[0063] Step A1: Use high-quality basalt rock supplemented with part of blast furnace slag and artificial blocks as raw materials, melt in a 1550°C furnace (thermal power combined with pool kiln), appropriately increase the furnace temperature to make the composition of the melt uniform, and fully volatilize the gas generated inside the melt.

[0064] Step A2: The molten liquid is formed into fibers by a high-speed four-roll centrifuge (the centrifuge speed is above 8000 rpm), and the fibers are effectively dispersed and de-slaged by a high-speed high-pressure blowing suspension device (the blowing speed needs to reach 200 m / s).

[0065] Step A3: spraying a dispersant of a mixed solution of epoxy resin and nano-SiO2 particle type modifier on the surface of the basalt fiber.

[0066] Step A4: Using a HiPerDiF device, add lignin fibers at 200°C and 2MP to prepare a composite fiber matrix.

[0067] Step A5: Use high-speed and high-pressure blowing suspension equipment to add organic reinforcement (polypropylene fiber), and the organic reinforcement is evenly mixed and coated on the surface of the matrix fiber to form composite fiber. In this embodiment, the mass ratio of basalt fiber, lignin fiber and polypropylene fiber is 6:1:1.

[0068] (2) Preparation of asphalt concrete

[0069] Step S1: The ore material determined according to the grading design is kept in an oven at 170°C for 3 hours;

[0070] Step S2: preheat the SBS modified asphalt to 175°C.

[0071] Step S3: adding the preheated mineral material and the novel composite fiber into the asphalt mixture mixing pot and dry mixing for 55 seconds.

[0072] Step S4: adding the SBS modified asphalt that has reached the preheating temperature into the mixing pot and stirring for 125 seconds to obtain a novel composite fiber anti-cracking reinforced asphalt mixture.

[0073] Embodiment 4

[0074] The composite fiber asphalt mixture of this embodiment includes, by weight, 70 parts of SBS modified asphalt, 600 parts of coarse aggregate, 300 parts of medium aggregate, 350 parts of fine aggregate, and 6 parts of composite fiber.

[0075] Preparation of composite fiber anti-cracking reinforced asphalt concrete, the specific implementation process is as follows:

[0076] (1) Preparation of composite fibers

[0077] Step A1: Use high-quality basalt rock supplemented with some blast furnace slag and artificial blocks as raw materials, melt them in a 1450°C furnace (thermal power combined with pool kiln), appropriately increase the furnace temperature to make the composition of the melt uniform, and fully volatilize the gas generated inside the melt.

[0078] Step A2: The molten liquid is formed into fibers by a high-speed four-roll centrifuge (the centrifuge speed is above 8000 rpm), and the fibers are effectively dispersed and de-slaged by a high-speed high-pressure blowing suspension device (the blowing speed needs to reach 200 m / s).

[0079] Step A3: spraying a dispersant of a mixed solution of epoxy resin and nano-SiO2 particle type modifier on the surface of the basalt fiber.

[0080] Step A4: Using a HiPerDiF device, add lignin fibers at 200°C and 2MP to prepare a composite fiber matrix.

[0081] Step A5: Use high-speed and high-pressure blowing suspension equipment to add organic reinforcement (polyester fiber), and the organic reinforcement is evenly mixed and coated on the surface of the matrix fiber to form composite fiber. In this embodiment, the mass ratio of basalt fiber, lignin fiber and polyester fiber is 12:1:3.

[0082] (2) Preparation of asphalt concrete

[0083] Step S1: The ore material determined according to the grading design is kept in an oven at 160° C. for 3.5 h;

[0084] Step S2: preheat the SBS modified asphalt to 165°C.

[0085] Step S3: adding the preheated mineral material and the novel composite fiber into the asphalt mixture mixing pot and dry mixing for 65 seconds.

[0086] Step S4: adding the SBS modified asphalt that has reached the preheating temperature into the mixing pot and stirring for 110 seconds to obtain a novel composite fiber anti-cracking reinforced asphalt mixture.

[0087] Embodiment 5

[0088] The composite fiber asphalt mixture of this embodiment includes, by weight, 70 parts of SBS modified asphalt, 600 parts of coarse aggregate, 300 parts of medium aggregate, 350 parts of fine aggregate, and 6 parts of composite fiber.

[0089] Preparation of composite fiber anti-cracking reinforced asphalt concrete, the specific implementation process is as follows:

[0090] (1) Preparation of composite fibers

[0091] Step A1: Use high-quality basalt rock supplemented with some blast furnace slag and artificial blocks as raw materials, melt them in a 1500°C furnace (thermal power combined with pool kiln), appropriately increase the furnace temperature to make the composition of the melt uniform, and fully volatilize the gas generated inside the melt.

[0092] Step A2: The molten liquid is formed into fibers by a high-speed four-roll centrifuge (the centrifuge speed is above 8000 rpm), and the fibers are effectively dispersed and de-slaged by a high-speed high-pressure blowing suspension device (the blowing speed needs to reach 200 m / s).

[0093] Step A3: spraying a dispersant of a mixed solution of epoxy resin and nano-SiO2 particle type modifier on the surface of the basalt fiber.

[0094] Step A4: Using a HiPerDiF device, add lignin fibers at 200°C and 2MP to prepare a composite fiber matrix.

[0095] Step A5: Use high-speed high-pressure blowing suspension equipment to add organic reinforcement (polypropylene fiber), and the organic reinforcement is evenly mixed and coated on the surface of the matrix fiber to form composite fiber. In this embodiment, the mass ratio of basalt fiber, lignin fiber and polypropylene fiber is 10:1:2.

[0096] (2) Preparation of asphalt concrete

[0097] Step S1: The ore material determined according to the grading design is kept in an oven at 170°C for 3 hours;

[0098] Step S2: preheat the SBS modified asphalt to 170°C.

[0099] Step S3: adding the preheated mineral material and the novel composite fiber into the asphalt mixture mixing pot and dry mixing for 70 seconds.

[0100] Step S4: adding the SBS modified asphalt that has reached the preheating temperature into the mixing pot and stirring for 130 seconds to obtain a novel composite fiber anti-cracking reinforced asphalt mixture.

[0101] In comparative example 1, the composite fiber is replaced with lignin fiber, 59.5 parts of SBS modified asphalt, 580 parts of coarse aggregate (10-15 mm graded crushed stone), 200 parts of medium aggregate (5-10 mm graded crushed stone), 220 parts of fine aggregate (2.6-3.5 machine-made sand), and 3.5 parts of lignin fiber.

[0102] In Comparative Example 2, the composite fiber was replaced with lignin fiber, 59.5 parts of SBS modified asphalt, 580 parts of coarse aggregate (10-15 mm graded crushed stone), 200 parts of medium aggregate (5-10 mm graded crushed stone), 220 parts of fine aggregate (2.6-3.5 machine-made sand), and 3.5 parts of lignin fiber.

[0103] The mixing method of the asphalt concrete in the above comparative example is the same as that in Example 1.

[0104] The asphalt concrete obtained above was used to prepare Marshall specimens. After natural curing, Marshall stability test, rutting test and splitting strength test were carried out according to JTG E20-2011 standard. The specific test results are shown in the following table:

[0105] Table 2 Asphalt mixture performance test results

[0106] Example 1 Example 2 Comparative Example 1 Comparative Example 2 Marshall stability / kN 9.47 13.37 8.56 14.62 <![CDATA[Dynamic stability / times·mm -1 > 6906 8163 6217 8356

[0107] From the data in Table 2, it can be seen that the Marshall stability and dynamic stability of the asphalt concrete of the embodiment are higher than those of comparative example 1, and lower than those of comparative example 2. The Marshall stability and dynamic stability of embodiment 1 are lower than those of embodiment 2, and the Marshall stability and dynamic stability of embodiment 2 are close to those of comparative example 2. This shows that the strengthening effect of the new composite fiber on asphalt concrete is better than that of lignin, but slightly lower than that of basalt fiber; the strengthening effect of the composite fiber prepared by polyester fiber on asphalt concrete is better than that of polypropylene fiber.

[0108] In order to verify the road crack resistance of the above asphalt concrete, the semicircular bending (low-temperature SCB) test was referred to and the test was carried out at -15°C. The fracture energy was used to characterize the low-temperature crack resistance of the asphalt mixture.

[0109] The three types of fibers were used to make asphalt mixture according to the above-mentioned asphalt mixture preparation process. A large Marshall specimen with a diameter of 150 mm was made by a rotary compaction equipment. It was cured at room temperature for 12 hours and further cut into semicircular specimens with a thickness of 45±5 mm and a diameter of 150±9 mm by a large cutting equipment. A 15 mm long seam was cut at the bottom of the semicircular specimen for a semicircular bending test.

[0110] Eight semicircular specimens were prepared for each group of three types of fibers and tested, and the average value was taken as the final result.

[0111] Table 3 Results of semicircular bending test of asphalt mixture at -15℃

[0112] radius thickness Fracture Energy Example 1 71.58 45.26 1056.53 Example 2 72.05 45.18 1658.34 Comparative Example 1 72.275 46.10 974.64 Comparative Example 2 72.30 43.50 1849.59

[0113] It can be seen from the data in Table 3 that, under the condition of -15°C, the low-temperature crack resistance of the embodiment is stronger than that of comparative example 1, but weaker than that of comparative example 2. The low-temperature crack resistance of embodiment 1 is weaker than that of embodiment 2, and the low-temperature crack resistance of embodiment 2 is close to that of comparative example 2.

[0114] The strengthening effect of the composite fiber prepared by polyester fiber on the low-temperature anti-cracking performance of asphalt mixture is significantly better than that of polypropylene fiber and is close to that of basalt fiber.

[0115] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A composite fiber for crack-resistant reinforced asphalt concrete, characterized in that: The composite fiber is a multilayer structure of inorganic fibers and organic fibers. The inorganic fibers and organic fibers are alternately stacked in layers to form a three-dimensional network structure matrix that is interwoven with each other. The surface of the three-dimensional network structure matrix is ​​wrapped with an organic reinforcement, and the organic reinforcement is also filled in the interlayer gaps between the inorganic fibers and the organic fibers.

2. The composite fiber for crack-resistant reinforced asphalt concrete according to claim 1, characterized in that: The inorganic fiber is modified basalt fiber, the organic fiber is lignin fiber, and the organic reinforcement is polyester fiber or polypropylene fiber.

3. The composite fiber for crack-resistant reinforced asphalt concrete according to claim 2, characterized in that: The modified basalt fiber is a basalt fiber on which a layer of organic film is bonded in the form of chemical bonds.

4. The composite fiber for crack-resistant reinforced asphalt concrete according to claim 3, characterized in that: The basalt fiber is modified by epoxy resin and nano-SiO2 particles.

5. The composite fiber for crack-resistant reinforced asphalt concrete according to claim 3, characterized in that: The thickness of the organic film is 10-30 nm.

6. The composite fiber for crack-resistant reinforced asphalt concrete according to claim 2, characterized in that: The mass ratio of the inorganic fiber, the organic fiber and the organic reinforcement is 6-12:1:1-3.

7. The composite fiber for crack-resistant reinforced asphalt concrete according to claim 1, characterized in that: The length of the composite fiber is 1-3 mm, and the mass percentage of flocculent fiber clusters is not less than 4.8%.

8. The method for preparing composite fibers for crack-resistant reinforced asphalt concrete according to claim 1, characterized in that: The following steps are involved: Basalt fiber is prepared by using basalt stone supplemented with part of blast furnace slag and artificial blocks as raw materials, and a mixed solution modifier of epoxy resin and nano-SiO2 particles is sprayed on the surface of the basalt fiber, and then mixed with lignin fiber at a temperature of 180-220°C, and finally organic reinforcement is added and mixed evenly.

9. A crack-resistant reinforced asphalt concrete, characterized in that: The asphalt concrete contains the composite fiber as claimed in claim 1, and the asphalt concrete raw materials include the following components by weight: 40-70 parts of SBS modified asphalt, 500-600 parts of coarse aggregate, 100-300 parts of medium aggregate, 250-350 parts of fine aggregate, and 1-6 parts of composite fiber.

10. The method for preparing crack-resistant reinforced asphalt concrete according to claim 9, characterized in that: The following steps are involved: S1, heating the aggregate to a temperature of 160°C-180°C and keeping it warm for 3-4 hours; S2, preheat the SBS modified asphalt to 165℃-175℃, then add the aggregate and composite fiber and mix well.

Citation Information

Cited By

  • Composite fiber and preparation process thereof

    CN122484960A